Paleoproterozoic Rocks of the Belcher Islands, Nunavut: A Review of Their Remarkable Geology and Relevance to Inuit-led Conservation Efforts - McDonald, Brayden; Partin, Camille (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2024)
The Paleoproterozoic Belcher Group (ca. 2.0 to 1.83 Ga) occurs on the remote Belcher Islands of Hudson Bay in Nunavut, Canada. It includes nearly nine kilometres of well-preserved siliciclastic and carbonate sedimentary rocks, deposited initially in a marginal to shallow marine setting representing one of the first true continental shelf environments on the proto-Canadian Shield. A wide variety of depositional facies exists within the Belcher Group, and it is particularly well known for its spectacular stromatolites in dolostone. In addition to these macroscopic features, two of its formations (Kasegalik and McLeary) contain intact microfossils of Eoentophysalis belcherensis, the oldest known occurrence of cyanobacteria in the geological record. The uppermost part of the Belcher Group contains sedimentary rocks of very different character that represent a younger foreland basin that developed in response to accretionary and collisional processes of the Trans-Hudson orogen. These younger formations (Omarolluk and Loaf) consist of a thick sequence of turbidites, overlain by arkose and other immature clastic sedimentary rocks. A defining characteristic of the Omarolluk Formation is the presence of calcareous concretions. The Omarolluk Formation shares attributes with “omars”, which are glacially transported clasts that occur both locally and further afield throughout parts of Canada and the northern United States and have helped characterize Pleistocene ice-flow trends across the continent.The Belcher Group also includes two formations dominated by spectacular mafic volcanic rocks. The earlier episode, represented by the Eskimo Formation, reflects eruption of largely subaerial volcanic flows interpreted to represent flood basalt associated with the rifting of Archean basement during the establishment of the continental shelf. A later volcanic episode (the Flaherty Formation) is dominated by submarine pillowed basalt flows and has been assigned to varied tectonic settings, including volcanic arcs related to subduction and oceanic plateaus related to mantle plume activity and renewed rifting along the continental margin. This later volcanism marks the transition from shelf to foreland basin. Mafic sills and related intrusions (Haig intrusions) occur in the middle and lower part of the Belcher Group. Thermal and chemical interactions between mafic magma and calcareous shale generated unusual rocks that are well known in Nunavut as high-quality artisanal carving stone. The Belcher Group also contains Superior-type iron formations that have attracted past exploration interest.The Belcher Group is a unique geological entity defined by its wide variety of rock types, its superb exposures, and its potential to illustrate many important geological processes in a formative time in Earth’s history. It is also a unique microfossil paleontological resource, and its deposition brackets a crucial and much-debated interval of Precambrian atmospheric and oceanic evolution. It represents an important scientific resource in the context of understanding such changes. This general review paper highlights its most important features, discusses its potential for future research and contributes to wider discussions about its possible future role as a protected area within Nunavut.